BIBLIOGRAPHIC STUDY OF THE USE OF BIOMASS ENERGY IN BRAZIL - Ricarte Saraiva, Jucier; de Oliveira Sousa, Juciara; Wilton de Medeiros Santos, José; do Socorro Batista, Maria; Barboza da Silva, Marquilene; Sarmento da Silva, Andressa; Raul Barbosa de Moura, Robson; Amaro Ribeiro Ferreira, Gizelia; Gonçalves Ribeiro, Rafael; Israel de Sousa Silva, José (Revista Gênero e Interdisciplinaridade, 2022)
Energy production is essential for the development of humanity, so it is verified that the more energy sources and technological detention of these energy sources will present the greater the level of development of this nation, but it must be verified that every country needs to worry about having sustainable sources of energy so that it is not dependent on sources that are not renewable, thus biomass is a source that presents itself as a possibility. The objectives are the following: to present a definition, applications of its terminologies, application by Brazil, its advantages, its categories. The methodology applied to the work was the bibliographic review method, consisting of the search for documents, books, articles and literature on the subject. The research verified that the use of biomass comes from the beginning of the formation of modern societies, having its apex during the first two industrial revolutions, and Brazil has a long history with sustainable sources of energy, as well as the country sees bioenergy as a secondary matrix. It is concluded that Brazil is a nation that does not show much interest in the production of such energy, however it has a significant biomass energy park.